The women behind the door - Doyle, Roddy 1958- (Jonathan Cape, 2024)
"Booker-Prize winner Roddy Doyle's spectacular return to his iconic heroine, Paula Spencer The undisputed laureate of ordinary lives'SUNDAY TIMES Brilliant...passionate, funny and humane'DAVID NICHOLLSAt sixty-six, Paula Spencer - mother, grandmother, widow, addict, survivor - is finally living her life. A job at the dry cleaners she enjoys, a man - Joe - with whom she shares what she wants, friends who see her for who she is, and four grown children, now with families and petty dramas the likes of which Paula could only have hoped for. Despite its ghosts, Paula has started to push her past aside.That is until Paula's eldest, Nicola, turns up on her doorstep. Independent, affluent, a loving wife and mother, a success - Nicola is suddenly determined to leave it all behind. Over the next few days, as Nicola gradually confides in Paula the secret that unleashed this moment of crisis, mother and daughter find themselves untangling anecdotes, jokes, memory and revelation to confront the bruised but beautiful symmetry of what each means to the other. Paula Spencer is a hymn to female generosity; the ordinary, discardable kind that keeps the world turning. Reading her voice for the first time sent a pang of recognition through me, followed by love'ANNE ENRIGHT."
Keywords: Fiktionale Darstellung